Impact of Sugar Reduction and PNPLA3 Genotype on Liver Fat, Liver Fibrosis, and Body Composition in Hispanic Youth With Obesity: A Randomized Controlled Trial. (7th June 2021) - Schmidt, Kelsey; Jones, Roshonda; Berger, Paige; Plows, Jasmine; Alderete, Tanya; Fogel, Jennifer; Hooman, Allayee; Nayak, Krishna; Sinatra, Frank; Harlan, Gregory; Goran, Michael
Abstract: Objectives: Pediatric Non-Alcoholic Fatty Liver Disease is prevalent among Hispanics, which may partially result from a higher frequency of the C > G polymorphism in the patatin-like phospholipase 3 (PNPLA3) gene. Our prior work showed an interaction between the GG genotype and high dietary sugar, resulting in higher liver fat. Additionally, studies show that extreme sugar depletion improves liver fat in children with obesity. This trial aimed to test whether a clinical intervention for sugar reduction versus standard diet advice in Hispanic youth differentially impacts liver fat, liver fibrosis, body weight and composition, and whether effects differed by PNPLA3 genotype. Methods: Hispanic youth with obesity ( n  = 105; 72% GG) were randomized to a healthy eating control group or a sugar reduction group (goal, <10% of calories from free sugar) for 12 weeks. Participants continued their typical exercise regimens and incorporated their interventions into their ad libitum diet. Liver fat and fibrosis were measured by magnetic resonance imaging and elastography, and body composition by dual energy x-ray absorptiometry before and after the intervention. Results: Both treatment and control groups reduced free sugar intake, with a greater reduction in the treatment group (−4.8 ± 6.5% vs. −3.0 ± 8.5%, P  = 0.02). At follow-up, free sugar intake in the intervention group was 8.8 ± 5.4% of calories. In modified intent to treat analyses, there were no differential intervention effects on liver fat, liver fibrosis, body weight, body fat or fat distribution ( P  > 0.05). No treatment by PNPLA3 genotype interaction was observed for any endpoint ( P  > 0.05). While there was no significant change in fat mass in either study arm, secondary analyses revealed that participants who reduced fat mass, significantly reduced liver fat compared to those without fat mass reduction [−1.8% (−6.2, −3.4) vs. 0.3% (−1.0, 1.1), P  < 0.001]. Conclusions: In Hispanic Youth with obesity, a clinic-based intervention focused on sugar reduction did not affect liver fat, liver fibrosis, body weight or composition, regardless of PNPLA3 genotype. However, the reduction in sugar intake observed might not have been sufficient to shift liver fat. Further, our results suggest that reducing fat mass is essential to reducing liver fat. Funding Sources: The National Institute on Minority Health and Health Disparities (MD-010358).